Wadalite and method for producing Wadalite
The method of producing Wadalite using weathered black cloud mother and metal chloride at lower temperatures addresses environmental concerns and substrate restrictions, resulting in high-purity Wadalite production.
Patent Information
- Application Number
- JP2023101148
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2043-06-20
AI Technical Summary
The existing manufacturing methods for Wadalite involve high-temperature processes that result in significant environmental impact and restrict the choice of substrates due to heat resistance concerns.
A manufacturing method that utilizes a mixture of clay minerals, particularly weathered black cloud mother, with metal chloride as a molten salt at reduced temperatures through a process involving crushing, adsorption of metal ions, mixing, and controlled heat treatment.
Enables the production of Wadalite with reduced environmental impact and increased substrate flexibility, achieving high purity and efficiency in manufacturing.
Smart Images

Figure 0007625289000001 
Figure 0007625289000002 
Figure 0007625289000003
Abstract
Description
[Technical field]
[0001] The present invention relates to wadalite and a method for producing wadalite. [Background technology]
[0002] Wadalite is used in humidity sensors and the like because it has good proton conductivity due to the water adsorbed on its surface. On the other hand, in the manufacturing method of Wadalite, the heat treatment in the manufacturing process is performed at high temperatures. When the heat treatment is performed at high temperatures, not only does it increase the environmental load, but it also greatly restricts the types of substrates that can be used during manufacturing, making it difficult to manufacture easily.
[0003] Patent Document 1 discloses a method for producing a wadalite compound, which is capable of forming a film of the wadalite compound on a substrate without being restricted much by the heat resistance of the substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-23400 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the manufacturing method disclosed in Patent Document 1, in the process before forming wadalite on the substrate, the amorphous material that is the raw material of wadalite must be held at a high temperature of 1450°C to 1800°C to melt and then quenched. Furthermore, the manufacturing method disclosed in Patent Document 1 requires that the quenched material be heat-treated at a temperature of less than 850°C. Therefore, the manufacturing method disclosed in Patent Document 1 is a manufacturing method that places a large burden on the environment and is time-consuming.
[0006] The present invention has been made in consideration of the above, and aims to obtain Wadalite easily with little environmental impact. [Means for solving the problem]
[0007] In order to solve the above problems, the manufacturing method of wadalite according to the present invention includes a mixing step of mixing a clay mineral with salt to obtain a mixture, and a heat treatment step of heat treating the mixture, wherein the clay mineral is a weathered layered clay mineral, and the salt is a metal chloride that becomes a molten salt in the heat treatment step. Effect of the Invention
[0008] According to the present invention, wadalite can be obtained by a simple method with a small environmental impact. [Brief description of the drawings]
[0009] [Figure 1] 1A to 1C are diagrams showing a method for manufacturing Wadalite according to the first embodiment. [Diagram 2] Figure showing the X-ray diffraction spectrum of weathered biotite. [Diagram 3] A graph showing the X-ray diffraction spectrum of biotite. [Figure 4] FIG. 2 is a diagram illustrating the effect of the adsorption process shown in FIG. 1 on clay minerals. [Diagram 5] A diagram showing the difference in X-ray diffraction spectra of weathered biotite with or without the adsorption of cesium ions. [Figure 6] A diagram showing the difference in the composition of weathered biotite depending on whether or not cesium ions are adsorbed. [Figure 7] FIG. 2 is a diagram showing the production conditions and results in Examples 1 to 5 and Comparative Examples 1 to 4 of the production method shown in FIG. [Figure 8] A comparison of the X-ray diffraction spectrum of the product of Example 1 shown in Figure 7 with the X-ray diffraction spectrum of Wadalite. [Figure 9] A comparison of the X-ray diffraction spectrum of the product of Example 2 shown in Figure 7 with the X-ray diffraction spectrum of Wadalite. [Figure 10] A figure comparing the X-ray diffraction spectrum of the product of Comparative Example 1 shown in Figure 7 with the X-ray diffraction spectrum of Wadalite. [Figure 11] 8 showing the X-ray diffraction spectrum of the product of Example 1, and the main peak of FIG. 9 showing the X-ray diffraction spectrum of the product of Example 2. FIG. [Figure 12] FIG. 8 is a diagram showing the results of analyzing the compositions of the products of Examples 1 to 5 and Comparative Examples 1 to 4 shown in FIG. 7 by fluorescent X-ray analysis. [Figure 13] A figure comparing the X-ray diffraction spectrum of the product in Example 6 of the manufacturing method according to the second embodiment with the X-ray diffraction spectrum of Wadalite. [Figure 14] FIG. 11 is a diagram showing a method for producing a thermoelectric conversion material according to a third embodiment. [Figure 15] FIG. 15 is a diagram showing the production conditions in Examples 7 to 11 and Comparative Example 5 of Production Method 1 shown in FIG. [Figure 16] FIG. 16 is a graph showing the measurement results of the electrical conductivity of each of the products of Examples 7 to 11 and Comparative Example 5 shown in FIG. 15. [Figure 17] FIG. 16 is a graph showing the measurement results of the Seebeck coefficient of each product of Examples 7 to 11 and Comparative Example 5 shown in FIG. [Figure 18] FIG. 16 is a graph showing the results of measuring the thermal diffusivity of each of the products of Examples 7 to 11 and Comparative Example 5 shown in FIG. [Figure 19] FIG. 16 is a graph showing the evaluation results of the dimensionless figure of merit ZT of each of the products of Examples 7 to 11 and Comparative Example 5 shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present invention will be described with reference to the drawings. In the embodiments, the same reference numerals denote the same configurations or functions, and unless otherwise specified, the description thereof will be omitted.
[0011] [First embodiment] A method 1 for manufacturing a Wadalite according to the first embodiment will be described with reference to Figures 1 to 12. Figure 1 is a diagram showing a method 1 for manufacturing a Wadalite according to the first embodiment.
[0012] The features of the wadalite manufacturing method 1 in this embodiment are that it uses a clay mineral that is abundant in nature as a starting material, and that wadalite can be produced at a lower temperature than conventional methods by heat treatment after mixing the clay mineral with salt.
[0013] As shown in Fig. 1, the production method 1 according to this embodiment includes a crushing and classification step S1 in which a clay mineral as a starting material is crushed and classified, and an adsorption step S2 in which a predetermined metal element is adsorbed onto the classified clay mineral. Furthermore, the production method 1 according to this embodiment includes a mixing step S3 in which a salt is mixed with the clay mineral to obtain a mixture, and a heat treatment step S4 in which the mixture is heat treated.
[0014] <Starting materials> Figure 2 shows the X-ray diffraction spectrum of weathered biotite. Figure 3 shows the X-ray diffraction spectrum of biotite.
[0015] The clay mineral as the starting material is a layered clay mineral. Examples of the layered clay mineral include 1:1 type clay minerals and 2:1 type clay minerals. Specific examples of the 1:1 type clay minerals include serpentine group (e.g., kaolinite). Specific examples of the 2:1 type clay minerals include talc-pyrophyllite group (e.g., talc), smectite group (e.g., montmorillonite), vermiculite group (e.g., weathered biotite), mica group (e.g., biotite, illite, biotite), brittle mica group, or chlorite group.
[0016] The clay mineral, which is the starting material of the manufacturing method 1 according to this embodiment, is preferably a weathered layered clay mineral, and in particular, weathered biotite. Weathered biotite is a material that is abundant in nature and easily available. Biotite itself has a layered crystal structure in which thin sheet-like clay layers are stacked. Weathered biotite often swells so that the sheet-like clay layers peel off in a specific direction, especially the outer edge part, and is loosened. As a result, the clay layers of the weathered biotite are spread between the layers, and cations can easily enter between the clay layers, and the reaction with salt in the heat treatment step S4 is easily promoted. Furthermore, metal elements are easily adsorbed to the weathered biotite in the adsorption step S2, and high purity wadalite can be easily produced as described later. For these reasons, weathered biotite is preferable as the starting material of the manufacturing method 1 according to this embodiment.
[0017] As shown in FIG. 2, the X-ray diffraction spectrum of weathered biotite has an asymmetric and broad peak at diffraction angles of about 6° to 10°. This is believed to be due to the disruption of the layered crystal structure of weathered biotite due to weathering. Since biotite has high crystallinity, the X-ray diffraction spectrum of biotite has a sharp peak as shown in FIG. 3. In other words, weathered biotite and biotite can be distinguished by comparing their X-ray diffraction spectra. The X-ray diffraction spectrum is a spectrum that represents the diffraction intensity measured by the X-ray diffraction method for each diffraction angle.
[0018] <Crushing / classification process S1> The clay mineral as the starting material may be in bulk, but in order to produce uniform wadalite with high efficiency, it is preferable to crush it to a predetermined particle size. The particle size of the clay mineral crushed in the crushing and classification step S1 is not particularly limited, and may be, for example, an average particle size of 5 μm or less, or may be an average particle size of more than 5 μm and 20 μm or less. The method of crushing the clay mineral in the crushing and classification step S1 is not particularly limited, and may be, for example, a crushing method using an automatic mortar.
[0019] The method of classifying the clay mineral in the pulverization and classification step S1 is not particularly limited, and may be, for example, a classification method using elutriation. The classification method using elutriation is a method of classifying the pulverized clay mineral by putting it in water, stirring it, removing impurities, and drying it. The classification method using elutriation is preferable in that it can produce a more uniform wadalite because it can obtain clay minerals of any particle size and remove impurities.
[0020] <Adsorption process S2> Fig. 4 is a diagram for explaining the influence of the adsorption step S2 shown in Fig. 1 on clay minerals. Fig. 5 is a diagram showing the difference in X-ray diffraction spectrum of weathered biotite depending on whether or not cesium ions are adsorbed. Fig. 6 is a diagram showing the difference in composition of weathered biotite depending on whether or not cesium ions are adsorbed.
[0021] In the adsorption step S2, a predetermined metal element ion is adsorbed to the clay mineral obtained in the pulverization and classification step S1. The adsorbed metal element is not particularly limited as long as it has an ionic radius equal to or larger than that of the metal (e.g., calcium) contained in the salt (e.g., calcium chloride) used in the subsequent mixing step S3 and heat treatment step S4. In other words, the ionic radius of the adsorbed metal element is equal to or larger than that of the metal contained in the salt mixed in the mixing step S3. Examples of the adsorbed metal element include sodium, potassium, rubidium, and cesium. When the clay mineral is weathered biotite, cesium is preferred as the adsorbed metal element.
[0022] In the adsorption step S2, first, as shown in FIG. 4(a), the metal element ion (cesium ion) to be adsorbed penetrates from the outer edge of the clay mineral into the gap between the clay layers constituting the clay mineral and is adsorbed. Then, as shown in FIG. 4(b), new metal element ions are adsorbed next to the adsorbed metal element ions, and as shown in FIG. 4(c), the metal element ions are continuously (or collectively) adsorbed between the clay layers. Then, as shown in FIG. 4(d), the adsorption of the mass of metal element ions causes the interlayer distance of the clay layers to which the metal element ions are adsorbed to shrink. Then, as shown in FIG. 4(e), the adjacent clay layers peel off, and surface adsorption sites for the metal element ions appear.
[0023] Due to the phenomenon shown in FIG. 4(a) to FIG. 4(e), in the adsorption step S2, metal element ions are adsorbed between the clay layers, the interlayer distance of the clay layers shrinks, and the interlayer distance of the clay layers becomes uniform in the direction along the clay layers. In fact, the interlayer distance of weathered biotite without cesium ion adsorption is about 10.54 Å, while the interlayer distance of weathered biotite with cesium ion adsorption is about 10.20 Å. Also, as shown in FIG. 5, it can be seen that the X-ray diffraction spectrum of weathered biotite with cesium ion adsorption has a sharper peak shape around 6 deg to 10 deg than the X-ray diffraction spectrum of weathered biotite without cesium ion adsorption. This is thought to be due to the fact that the order of the clay layers is increased by the adsorbed cesium ions, and the layered structure is arranged in the weathered biotite with cesium ion adsorption. Weathered biotite absorbs cesium ions, which have a large ionic radius, and exchanges them for potassium ions and other ions that were originally present between the clay layers. In fact, as shown in Figure 6, weathered biotite with cesium ions absorbed has an increased amount of cesium ions and a decreased amount of potassium ions compared to weathered biotite without cesium ion absorption.
[0024] When cesium ions are adsorbed between the clay layers of weathered biotite in the adsorption step S2, not only do cesium ions and ions with similar chemical properties easily adsorb to the interlayers, but also the interlayers spread uniformly. As a result, during the reaction between salt (e.g., calcium chloride) and weathered biotite in the subsequent heat treatment step S4, calcium ions with a large ionic radius easily penetrate deep into the interlayers of the clay layers and are easily exchanged for cesium ions adsorbed between the layers. Therefore, adsorbing cesium ions in the adsorption step S2 has the effect of promoting the reaction between weathered biotite and salt in the subsequent heat treatment step S4. However, the adsorption step S2 is not essential in the manufacturing method 1 according to this embodiment.
[0025] As a method for realizing the adsorption step S2, for example, there is a method in which a solution containing the metal element ions to be adsorbed (for example, a cesium chloride solution) is mixed with a clay mineral (for example, weathered biotite) to adsorb the metal element ions to the clay mineral. In this case, it is preferable to mix the metal element with the clay mineral so that the weight of the metal element is added to the weight of the clay mineral in a range of 2 wt% to 6 wt%. In this way, the adsorption step S2 can adsorb the metal element ions to the clay mineral without excess or deficiency. Specifically, for example, an elutriation material is dispersed in a cesium chloride solution, mixed with weathered biotite, and gently stirred overnight to obtain weathered biotite with cesium ions adsorbed thereon. In this case, the cesium chloride solution and weathered biotite may be mixed so that the weight of cesium is added to the weight of the weathered biotite in a range of 2 wt% to 6 wt%.
[0026] <Mixing process S3> In the mixing step S3, salt is mixed with the clay mineral obtained in the crushing and classification step S1 or the adsorption step S2 to obtain a mixture. The salt to be mixed is a metal chloride that will become a molten salt in the subsequent heat treatment step S4. This is because if the mixed salt becomes a molten salt when it becomes hot in the subsequent heat treatment step S4, it will act as an ion and can produce wadalite, but if the mixed salt sublimes when it becomes hot, wadalite cannot be produced. For example, calcium chloride is preferable as the salt to be mixed. For example, calcium chloride powder having an average particle size equivalent to that of calcium chloride powder manufactured by Showa Chemical Co., Ltd. and having product codes such as 0305-2250, 0305-2260, or 0305-2280 is preferable as the calcium chloride to be mixed.
[0027] In the mixing step S3, the clay mineral (for example, weathered biotite) obtained by the crushing and classification step S1 or the adsorption step S2 may be mixed with salt (for example, calcium chloride) in the same mass. Specifically, for example, weathered biotite and calcium chloride may be mixed in the same mass. This means that it is sufficient to prepare a large amount of calcium chloride to be reacted, and it is considered that this is due to the structural characteristics of weathered biotite, that is, the clay layer swells due to weathering and the interlayer space is expanded. In the conventional Patent Document 1 (JP Patent Publication 2013-23400 A), as described in paragraph 0067, a large amount of calcium chloride, four times that of the amorphous material, was required. In contrast, in the manufacturing method 1 according to the present embodiment, even if a smaller amount of salt than the conventional one is mixed, wadalite can be manufactured.
[0028] <Heat treatment step S4> In the heat treatment step S4, the mixture obtained in the mixing step S3 is heat-treated. Specifically, for example, a mixture of weathered biotite and calcium chloride is heated at a heat treatment temperature of 600°C or more and less than 850°C using a general electric furnace such as a circular electric furnace. The heat treatment time is not particularly limited, but may be, for example, 2 hours. After the heat treatment step S4, in the manufacturing method 1 according to the present embodiment, the heat-treated product obtained in the heat treatment step S4 is washed with water, separated into solid and liquid by centrifugation, the liquid phase is discarded, and the remaining solid phase is dried at 80°C to obtain wadalite.
[0029] When the mixture is a mixture of weathered biotite with cesium adsorption and calcium chloride, the heat treatment temperature in the heat treatment step S4 may be 600 ° C or more and less than 850 ° C. If the heat treatment temperature in the heat treatment step S4 is 700 ° C or more and less than 850 ° C, high purity wadalite can be produced, which is preferable. Also, when the mixture is a mixture of weathered biotite without cesium adsorption and calcium chloride, the heat treatment temperature in the heat treatment step S4 may be 700 ° C or more and less than 850 ° C. Wadalite can be produced even at a low heat treatment temperature of less than 850 ° C in the heat treatment step S4 because the clay layers of the weathered biotite have wide spaces between them, making it easy for calcium ions to enter between the layers and react with the weathered biotite.
[0030] In addition, when producing a film-like wadalite on a substrate, if the wadalite can be produced at a low temperature like the heat treatment process S4 of this embodiment, the heat resistance of the substrate is less restricted. Therefore, the production method 1 according to this embodiment is less restricted in the type of substrate used during production, the freedom of the production environment can be improved, and wadalite can be produced more easily.
[0031] <Example> Fig. 7 is a diagram showing the production conditions and results in Examples 1 to 5 and Comparative Examples 1 to 4 of the production method 1 shown in Fig. 1. In each result shown in Fig. 7, a circle indicates that wadalite was produced, a double circle indicates that high-purity wadalite was produced, and a cross indicates that wadalite could not be produced.
[0032] In Example 1, weathered biotite from Ono-machi, Fukushima Prefecture was prepared as the starting clay mineral, and the weathered biotite was crushed and classified by a crusher. The particle size of the crushed and classified weathered biotite was measured using a laser diffraction scattering method (Zetasizer Nano-ZS, a device manufactured by Malvern Panalytical Co., Ltd.), and the average particle size was 5 μm. In addition, the X-ray diffraction spectrum of the weathered biotite is as shown in FIG. 2, and it can be confirmed that it is crystalline. This is clearly different from the conventional Patent Document 1, which uses amorphous materials to produce wadalite.
[0033] Next, in Example 1, 0.5 g of the pulverized and classified weathered biotite was mixed with 0.5 g of calcium chloride and stirred to obtain a homogeneously mixed mixture. That is, in Example 1, the same mass of calcium chloride was mixed with the weathered biotite without cesium ion adsorption to obtain a mixture. The obtained mixture was subjected to a heat treatment at a heat treatment temperature of 700°C for a heat treatment time of 2 hours. The heat-treated product obtained by the heat treatment was washed with water and subjected to solid-liquid separation by centrifugation, after which the liquid phase was discarded, and the remaining solid phase was dried at 80°C to obtain the product of Example 1.
[0034] Next, the X-ray diffraction spectrum of the product of Example 1 was measured by powder X-ray diffraction method and compared with the X-ray diffraction spectrum of Wadalite.
[0035] Fig. 8 is a diagram comparing the X-ray diffraction spectrum of the product of Example 1 shown in Fig. 7 with the X-ray diffraction spectrum of Wadalite. In Fig. 8, the gray line shows the X-ray diffraction spectrum of the product of Example 1, and the dashed line shows the X-ray diffraction spectrum of Wadalite.
[0036] As shown in FIG. 8, the X-ray diffraction spectrum of the product of Example 1 had a main peak with the highest diffraction intensity at a diffraction angle of about 33 deg, and matched the X-ray diffraction spectrum of wadalite. The X-ray diffraction spectrum of the product of Example 1 also matched the X-ray diffraction spectrum of wadalite for peaks other than the main peak. Therefore, it was confirmed that the product of Example 1 was wadalite. However, the X-ray diffraction spectrum of the product of Example 1 has a peak at about 6 deg to 10 deg. This peak is a peak derived from the layered structure of weathered biotite. In other words, it was confirmed that the product of Example 1 was mostly wadalite, but that the layered structure of weathered biotite remained in a part of it.
[0037] In Example 2, a cesium chloride solution was mixed with the weathered biotite that had been crushed and classified in the same manner as in Example 1, and cesium ions were adsorbed onto the weathered biotite. At this time, the cesium chloride solution was mixed with the weathered biotite so that 4.0 wt% of cesium was added relative to the weight of the weathered biotite. Other production conditions in Example 2 were the same as those in Example 1.
[0038] 9 is a diagram comparing the X-ray diffraction spectrum of the product of Example 2 shown in FIG. 7 with the X-ray diffraction spectrum of Wadalite. In FIG. 9, the gray line shows the X-ray diffraction spectrum of the product of Example 2, and the dashed line shows the X-ray diffraction spectrum of Wadalite.
[0039] As shown in FIG. 9, the X-ray diffraction spectrum of the product of Example 2 had a main peak with the highest diffraction intensity at a diffraction angle of about 33 deg, and matched the X-ray diffraction spectrum of wadalite. The X-ray diffraction spectrum of the product of Example 2 also matched the X-ray diffraction spectrum of wadalite for peaks other than the main peak. Furthermore, the X-ray diffraction spectrum of the product of Example 2 did not have a peak derived from the layered structure of weathered biotite that appears around 6 deg to 10 deg. Therefore, it was confirmed that the product of Example 2 had a completely disappeared layered structure of weathered biotite, and was a wadalite of higher purity than that of Example 1.
[0040] In Example 3, a mixture of weathered biotite with cesium ion adsorption and calcium chloride was heat-treated at 600° C. for 2 hours. Other production conditions in Example 3 were the same as those in Example 2.
[0041] The X-ray diffraction spectrum of the product of Example 3 has peaks derived from the layered structure of weathered biotite, similar to the X-ray diffraction spectrum of the product of Example 1, but most of the peaks, including the main peak, matched the X-ray diffraction spectrum of wadalite. It was confirmed that the product of Example 3 was mostly wadalite, but that the layered structure of weathered biotite remained in a part of it.
[0042] In Example 4, the weathered biotite was mixed with a cesium chloride solution so that 2.2 wt% of cesium was added to the weight of the weathered biotite, and cesium ions were adsorbed on the weathered biotite. The other production conditions in Example 4 were the same as those in Example 2.
[0043] The X-ray diffraction spectrum of the product of Example 4 did not have a peak derived from the layered structure of weathered biotite, similar to the X-ray diffraction spectrum of the product of Example 2, and matched the X-ray diffraction spectrum of wadalite. It was confirmed that the product of Example 4 was high-purity wadalite.
[0044] In Example 5, a mixture of weathered biotite with cesium ion adsorption and calcium chloride was heat-treated at 600° C. for 2 hours. Other production conditions in Example 5 were the same as those in Example 4.
[0045] The X-ray diffraction spectrum of the product of Example 5 has peaks derived from the layered structure of weathered biotite, similar to the X-ray diffraction spectra of the products of Examples 1 and 3, but most of the peaks, including the main peak, matched the X-ray diffraction spectrum of wadalite. It was confirmed that the product of Example 5 was mostly wadalite, but that the layered structure of weathered biotite remained in a part of it.
[0046] In Comparative Example 1, biotite from India was prepared as the clay mineral starting material, and the biotite was crushed and classified in a crusher in the same manner as in Example 1. Other production conditions in Comparative Example 1 were the same as in Example 1.
[0047] Fig. 10 is a diagram comparing the X-ray diffraction spectrum of the product of Comparative Example 1 shown in Fig. 7 with the X-ray diffraction spectrum of Wadalite. In Fig. 10, the gray line shows the X-ray diffraction spectrum of the product of Comparative Example 1, and the dashed line shows the X-ray diffraction spectrum of Wadalite.
[0048] As shown in Fig. 10, the X-ray diffraction spectrum of the product of Comparative Example 1 did not have a main peak at a diffraction angle of about 33 deg, and did not match the X-ray diffraction spectrum of wadalite. Therefore, it was confirmed that the product of Comparative Example 1 was not wadalite. The inventors confirmed that pyroxene (pyroxene) or hematite (hematite) was produced under the production conditions of Comparative Example 1.
[0049] In Comparative Example 2, a mixture of weathered biotite without cesium ion adsorption and calcium chloride was subjected to heat treatment at 600° C. for 2 hours. Other production conditions in Comparative Example 2 were the same as those in Example 1.
[0050] The X-ray diffraction spectrum of the product of Comparative Example 2 did not have a main peak at a diffraction angle of about 33 deg, and did not match the X-ray diffraction spectrum of wadalite. It was confirmed that the product of Comparative Example 2 mostly maintained the layered structure of weathered biotite and was not wadalite.
[0051] In Comparative Example 3, a mixture of weathered biotite with cesium ion adsorption and calcium chloride was heat-treated at 500° C. for 2 hours. Other production conditions in Comparative Example 3 were the same as those in Example 2.
[0052] The X-ray diffraction spectrum of the product of Comparative Example 3 did not have a main peak at a diffraction angle of about 33 deg, and did not match the X-ray diffraction spectrum of wadalite. It was confirmed that the product of Comparative Example 3 mostly maintained the layered structure of weathered biotite and was not wadalite.
[0053] In Comparative Example 4, a mixture was obtained by mixing 10 times the mass of calcium chloride with the weathered biotite having cesium ions adsorbed thereon. The other production conditions in Comparative Example 4 were the same as those in Comparative Example 3.
[0054] The X-ray diffraction spectrum of the product of Comparative Example 4 did not have a main peak at a diffraction angle of about 33 deg, and did not match the X-ray diffraction spectrum of wadalite. Most of the product of Comparative Example 4 maintained the layered structure of weathered biotite, and it was confirmed that it was not wadalite.
[0055] <Considerations on the Examples> From the results of Example 1, Comparative Example 1, and Comparative Example 2, it is understood that when the clay mineral is biotite, wadalite cannot be produced at a heat treatment temperature of 700° C. or less, but when the clay mineral is weathered biotite, wadalite can be produced at a heat treatment temperature of 700° C. or more. This is because, as described above, the clay layers of weathered biotite are swollen due to weathering and the gaps between the layers are expanded, so that cations can easily enter between the clay layers, and the reaction with salt in the heat treatment step S4 is easily promoted.
[0056] From the results of Examples 1 and 2, it is understood that it is possible to produce high-purity wadalite by adsorbing cesium ions to weathered biotite. As described above, this is because the adsorption of cesium ions not only makes it easier for ions with similar chemical properties to cesium ions to be adsorbed between the layers, but also because the layers are uniformly spread out, the ions can easily penetrate deep between the clay layers, facilitating the reaction with salt in the heat treatment step S4.
[0057] From the results of Examples 1 and 3, it is understood that by adsorbing cesium ions to weathered biotite, it is possible to produce wadalite even if the heat treatment temperature is lowered to 600°C. As described above, this is thought to be due to the fact that the adsorption of cesium ions easily promotes the reaction with salt in the heat treatment step S4. In other words, the heat treatment temperature can be lowered by adsorbing cesium ions.
[0058] The results of Comparative Example 3 and Comparative Example 4 show that when the heat treatment temperature is 500° C., wadalite cannot be produced even if the amount of calcium chloride is increased by 10 times.
[0059] From these findings, it was found that it is important to use weathered layered clay minerals (e.g., weathered biotite) in order to produce wadalite at a low heat treatment temperature of 700°C. Furthermore, it was found that it is important to adsorb metal element ions (e.g., cesium ions) to the weathered layered clay minerals in order to lower the heat treatment temperature.
[0060] FIG. 11 is a diagram comparing the main peaks in FIG. 8 showing the X-ray diffraction spectrum of the product of Example 1 with the main peaks in FIG. 9 showing the X-ray diffraction spectrum of the product of Example 2.
[0061] 11, the main peak of the product of Example 1 had a full width at half maximum (FWHM) of 0.258 and a diffraction intensity of about 7000 cps (counts per second), whereas the main peak of the product of Example 2 had a full width at half maximum (FWHM) of 0.197 and a diffraction intensity of about 8000 cps.
[0062] In other words, the main peak of Example 2, in which high-purity wadalite was produced that does not have a peak derived from the layered structure of weathered biotite, has a smaller half-width and higher diffraction intensity than the main peak of Example 1, in which wadalite was produced that has the peak derived from the layered structure of weathered biotite.
[0063] Here, if impurities are present inside the crystal, X-rays are scattered inside the crystal during measurement by X-ray diffraction, so the diffraction intensity peak becomes broad and the diffraction intensity of the peak becomes low. Therefore, if impurities are present inside the crystal, the half-width of the main peak tends to increase. In addition, if the impurities inside the crystal have variations, the diffraction angle also variance occurs, so the half-width of the main peak tends to increase further. Therefore, it can be considered that the smaller the half-width of the main peak and the higher the diffraction intensity, the higher the purity of the wadalite.
[0064] Therefore, by evaluating not only the peak derived from the layered structure of weathered biotite but also the half-width and diffraction intensity of the main peak, it is possible to accurately determine whether high-purity wadalite has been produced.
[0065] In addition, from the results of Examples 1 and 2 and from FIG. 11 and the like, it is possible to produce wadalite having a main peak half width (FWHM) of 0.197 or more and 0.258 or less by subjecting a mixture of weathered biotite and calcium chloride in the same mass to a heat treatment temperature of 700° C. or more and less than 850° C. In other words, the wadalite produced by the production method 1 according to this embodiment includes wadalite having a main peak half width (FWHM) of 0.197 or more and 0.258 or less.
[0066] FIG. 12 is a diagram showing the results of analyzing the composition of each of the products of Examples 1 to 5 and Comparative Examples 1 to 4 shown in FIG. 7 by fluorescent X-ray analysis.
[0067] In Examples 1 to 5, naturally occurring weathered biotite is used as the starting material, and therefore, it is understood that the wadalite produced in Examples 1 to 5 contains at least one element of iron, magnesium, titanium, potassium, and manganese. That is, the wadalite produced by the production method 1 according to the present embodiment includes wadalite containing at least one element of iron, magnesium, titanium, potassium, and manganese.
[0068] Figure 12 also shows the results of analyzing the composition of weathered biotite without cesium ion adsorption, weathered biotite with cesium ion adsorption, and biotite by X-ray fluorescence analysis. It can be seen that the proportion of elements such as iron is smaller in weathered biotite than in biotite. This is thought to be due to the leaching of elements such as iron caused by the weathering of biotite.
[0069] [Second embodiment] A method for manufacturing a Wadalite according to the second embodiment will be described with reference to Fig. 13. In the method for manufacturing a Wadalite according to the second embodiment, the description of the same configuration as in the first embodiment will be omitted.
[0070] The manufacturing method 1 of Wadalite according to the second embodiment is different from that of the first embodiment in the adsorption step S2, and the steps other than the adsorption step S2 are the same as those of the first embodiment.
[0071] That is, in the adsorption process S2 according to the first embodiment, a solution containing the metal element ions to be adsorbed (e.g., a cesium chloride solution) is mixed with a clay mineral (e.g., weathered biotite) to adsorb the metal element ions onto the clay mineral.
[0072] In contrast, in the adsorption step S2 according to the second embodiment, a metal element is mixed with a clay mineral and heat-treated to cause the metal element ions to be adsorbed onto the clay mineral. Specifically, in the adsorption step S2 according to the second embodiment, for example, cesium chloride powder is mixed with weathered biotite and heat-treated to cause the cesium ions to be adsorbed onto the weathered biotite.
[0073] <Example> In Example 6, which is an example of the manufacturing method 1 according to the second embodiment, weathered biotite was prepared by pulverizing and classifying it in the same manner as in Example 2 shown in FIG. 7. Then, in Example 6, the weathered biotite was mixed with cesium chloride powder in the same mass, and heat-treated at a heat treatment temperature of 700° C. for 2 hours, and then washed with water to remove excess salt. In this way, a powder material of weathered biotite with cesium ions adsorbed thereon was obtained. In the obtained powder material, the adsorption ratio of cesium ions to the weathered biotite was 13.0 wt % in terms of the weight of cesium relative to the weight of the weathered biotite. The other manufacturing conditions in Example 6 were the same as those in Example 2.
[0074] Furthermore, the inventors have confirmed that according to the adsorption process S2 of embodiment 2, cesium ions can be adsorbed onto the weathered biotite so that cesium is added in an amount of 13.0 wt% or more and 15 wt% or less based on the weight of the weathered biotite.
[0075] 13 is a diagram comparing the X-ray diffraction spectrum of the product in Example 6 of the manufacturing method 1 according to the second embodiment with the X-ray diffraction spectrum of Wadalite. In FIG. 13, the gray line shows the X-ray diffraction spectrum of the product in Example 6, and the dashed line shows the X-ray diffraction spectrum of Wadalite.
[0076] The X-ray diffraction spectrum of the product of Example 6 did not have a peak derived from the layered structure of weathered biotite, similar to the X-ray diffraction spectrum of the product of Example 2, and matched the X-ray diffraction spectrum of wadalite. It was confirmed that the product of Example 6 was high-purity wadalite.
[0077] The adsorption step S2 in the second embodiment involves heat treatment, and therefore does not require stirring of the cesium chloride solution mixed with weathered biotite, so that cesium ions can be adsorbed onto the weathered biotite in a shorter time than in the first embodiment.
[0078] [Third embodiment] A method 1 for producing a thermoelectric conversion material according to the third embodiment will be described with reference to Figures 14 to 19. In the method 1 according to the third embodiment, the description of the same configuration as in the first embodiment will be omitted.
[0079] FIG. 14 is a diagram showing a method 1 for producing a thermoelectric conversion material according to the third embodiment.
[0080] The manufacturing method 1 according to the third embodiment is a method for manufacturing a thermoelectric conversion material by adding a pressure molding step S5 and a sintering step S6 to the manufacturing method 1 according to the first embodiment.
[0081] Specifically, the manufacturing method 1 according to the third embodiment may have the same pulverization and classification step S1 and heat treatment step S4 as those of the first embodiment. The manufacturing method 1 according to the third embodiment can manufacture a thermoelectric conversion material regardless of the presence or absence of the adsorption step S2. That is, the manufacturing method 1 according to the third embodiment may have the same adsorption step S2 as the first or second embodiment, but may not have the adsorption step S2 from the viewpoint of process simplification. The manufacturing method 1 according to the third embodiment differs from the first embodiment in the mixing step S3. The manufacturing method 1 according to the third embodiment has a pressure molding step S5 and a sintering step S6 added to the first embodiment. Hereinafter, the manufacturing method 1 according to the third embodiment, which has steps different from those of the first embodiment, will be described.
[0082] <Mixing process S3> In the mixing step S3, one or more kinds of alkali metal chlorides are mixed with the clay mineral obtained by the pulverization and classification step S1 to obtain a mixture. The alkali metal salt to be mixed is not particularly limited, but is preferably, for example, calcium chloride, sodium chloride, potassium chloride, or magnesium chloride. For example, the melting points of calcium chloride, potassium chloride, and magnesium chloride are about 700°C to 800°C, but the eutectic temperature of a mixed salt obtained by mixing two or more kinds of alkali metal chlorides is lowered at a specific mixing ratio. Therefore, the mixed salt can be expected to have an effect of lowering the reaction temperature with the clay mineral. Furthermore, the mixed salt can produce a thermoelectric conversion material showing any performance by adjusting the mixing ratio. For this reason, the mixing step S3 is a characteristic step of the manufacturing method 1 according to this embodiment.
[0083] <Pressure molding process S5> In the manufacturing method 1 according to the third embodiment, as in the first embodiment, the heat-treated product obtained in the heat treatment step S4 is washed with water, solid-liquid separation is performed by centrifugation, and the remaining solid phase is dried to obtain a powder material (wadalite). In the pressure molding step S5, the powder material is subjected to a pressure molding process to obtain a molded product. Specifically, in the pressure molding step S5, for example, the powder material is placed in a tablet molder with a diameter of 16 mm, and pressed with a load of 10 T by a hydraulic press to pressure mold into a pellet shape.
[0084] The pressure molding step S5 can reduce the amount of voids remaining inside the molded product. This makes it possible to suppress the expansion of voids remaining inside the molded product due to the influence of heat during the subsequent firing step S6, which causes cracking or distortion of the molded product. The pressure molding step S5 can be performed to a degree that can reduce the voids remaining inside the molded product as much as possible, and the method is not particularly limited. The pressure molding step S5 may be performed together with the firing step S6.
[0085] <Baking process S6> In the firing step S6, the molded product obtained in the pressure molding step S5 is heat-treated again to fire the molded product. Specifically, in the firing step S6, a general electric furnace such as a circular electric furnace is used to heat the molded product to a predetermined firing temperature at a heating rate of 100°C / h to 200°C / h, and the firing temperature is maintained for a predetermined firing time to fire the molded product. The firing temperature is not particularly limited, but may be, for example, 900°C to 950°C. The firing time is not particularly limited, but may be, for example, 5 hours.
[0086] Regarding the heating rate, if the temperature is raised rapidly, the voids in the molded product will escape to the outside rapidly, which is undesirable as it may cause cracks or distortion. Since the molded product has low thermal conductivity, it is necessary to strictly control the heating rate conditions. As a result of repeated experiments, the inventors have found that if the heating rate exceeds 200°C / h, cracks or the like will occur in the molded product. For this reason, the heating rate is preferably 200°C / h or less. From the viewpoint of shortening the manufacturing time, it is more preferable that the heating rate is 100°C / h or more and 200°C / h or less. As described above, since the cracks or distortions of the molded product are thought to be due to the voids inside the molded product, it is important to thoroughly dry the moisture of the molded product. The manufacturing method 1 according to the third embodiment may have a drying step for thoroughly drying the molded product before the firing step S6.
[0087] <Example> FIG. 15 is a diagram showing the production conditions in Examples 7 to 11 and Comparative Example 5 of Production Method 1 shown in FIG.
[0088] In Example 7, weathered biotite was prepared as a clay mineral starting material, and the weathered biotite was crushed and classified using a crusher. The particle size of the crushed and classified weathered biotite was measured using a laser diffraction scattering method (Zetasizer Nano-ZS, a device manufactured by Malvern Panalytical Co., Ltd.), and the average particle size was 5 μm.
[0089] Next, in Example 7, 0.5 g of the pulverized and classified weathered biotite was mixed with 0.5 g of calcium chloride and stirred to obtain a homogeneously mixed mixture. That is, in Example 7, the same mass of weathered biotite and calcium chloride were mixed to obtain a mixture. The obtained mixture was heat-treated at a heat treatment temperature of 700°C for a heat treatment time of 2 hours. The heat-treated product obtained by the heat treatment was washed with water and separated into solid and liquid by centrifugation, after which the liquid phase was discarded, and the remaining solid phase was dried at 80°C to obtain a powder material.
[0090] Next, in Example 7, the obtained powder material was placed in a tablet molder with a diameter of 16 mm, and pressed into a pellet shape by a hydraulic press with a load of 10 T to obtain a molded product. Next, in Example 7, the obtained molded product was heat-treated again with a heating rate of 100°C / h, a firing temperature of 950°C, and a firing time of 5 hours, and the molded product was fired. After that, the obtained fired product was naturally cooled to obtain the product of Example 7.
[0091] In Example 8, 0.5 g of weathered biotite crushed and classified in the same manner as in Example 7 was uniformly mixed with 0.5 g of a mixed salt in which calcium chloride and sodium chloride were mixed in a ratio of calcium chloride:sodium chloride=1:1 to obtain a mixture. The other production conditions in Example 8 were the same as those in Example 7.
[0092] In Example 9, calcium chloride and potassium chloride were selected as the mixed salt, and the mixing ratio of calcium chloride:potassium chloride was 1: 1. Other production conditions in Example 9 were the same as those in Example 8.
[0093] In Example 10, the mixing ratio of the mixed salts was calcium chloride:potassium chloride=1:3. Other production conditions in Example 10 were the same as those in Example 9.
[0094] In Example 11, the mixing ratio of the mixed salts was calcium chloride:potassium chloride=3:1. Other production conditions in Example 11 were the same as those in Example 9.
[0095] In Comparative Example 5, the heat treatment in the heat treatment step S4 was carried out without mixing salt with weathered biotite, which is a clay mineral. Other production conditions in Comparative Example 5 were the same as those in Example 7.
[0096] 16 to 19, the performance evaluation of each product of Examples 7 to 11 and Comparative Example 5 shown in FIG. 15 will be described.
[0097] The performance of thermoelectric materials can be evaluated using the dimensionless figure of merit ZT of the thermoelectric material. The dimensionless figure of merit ZT is ZT=S 2 It is expressed by the formula σT / κ, where S is the Seebeck coefficient of the thermoelectric conversion material, T is the absolute temperature of the thermoelectric conversion material, σ is the electrical conductivity of the thermoelectric conversion material, and κ is the thermal conductivity of the thermoelectric conversion material. Thermal conductivity κ can be calculated by multiplying the specific heat and density by the thermal diffusivity. Therefore, in order to evaluate the performance of each product of Examples 7 to 11 and Comparative Example 5, the electrical conductivity [S / cm], Seebeck coefficient [μV / K], thermal diffusivity [mm 2 / s] was measured, and ZT in the temperature range was calculated.
[0098] Fig. 16 is a diagram showing measurement results of electrical conductivity of each product of Examples 7 to 11 and Comparative Example 5 shown in Fig. 15. Fig. 17 is a diagram showing measurement results of Seebeck coefficient of each product of Examples 7 to 11 and Comparative Example 5 shown in Fig. 15. Fig. 18 is a diagram showing measurement results of thermal diffusivity of each product of Examples 7 to 11 and Comparative Example 5 shown in Fig. 15. Fig. 19 is a diagram showing evaluation results of dimensionless figure of merit ZT of each product of Examples 7 to 11 and Comparative Example 5 shown in Fig. 15.
[0099] Generally, the electrical conductivity of clay minerals at room temperature is 10 -13 16, the conductivity of each product of Examples 7 to 11 is on the order of 10 -5It is improved by an order of magnitude. From the equation for the dimensionless figure of merit ZT, it is clear that an improvement in electrical conductivity contributes to an improvement in the dimensionless figure of merit ZT. Therefore, it can be said that each of the products of Examples 7 to 11 has improved thermoelectric conversion performance compared to simple clay minerals. Furthermore, as shown in FIG. 19, the dimensionless figure of merit ZT of each of the products of Examples 7 to 11 shows fluctuations in the high temperature region (from 650°C to 850°C). Therefore, it was confirmed that each of the products of Examples 7 to 11 is useful as a thermoelectric conversion material.
[0100] There are few cases where conventional thermoelectric conversion materials have been evaluated for their thermoelectric performance in high temperature ranges. This is because many conventional thermoelectric conversion materials are structurally unstable in high temperature ranges, and thermoelectric performance cannot be expected. In addition, there was a concern that conventional thermoelectric conversion materials would crack or deform due to the effects of heat when placed in a high-temperature environment.
[0101] In contrast, the products of Examples 7 to 11 exhibit performance as a thermoelectric conversion material even in a high temperature range, as shown in Fig. 19. In addition, because clay minerals are used as starting materials, which are also used for pottery, they are less susceptible to heat and have heat resistance, making them suitable for use in high temperature ranges. Therefore, the manufacturing method 1 according to the third embodiment can manufacture a thermoelectric conversion material that can be used in a high temperature range.
[0102] <Considerations on the Examples> From the evaluation results of Examples 7 to 11 and Comparative Example 5, it was found that the dimensionless figure of merit ZT was improved by mixing one or more types of alkali metal chlorides than by not mixing an alkali metal salt. Therefore, it is found that the inclusion of the mixing step S3 in which one or more types of alkali metal salts are mixed has a favorable effect on the thermoelectric conversion performance. This is considered to be due to the additive contribution of the electronic conduction carried by the conduction electrons and holes and the ionic conduction carried by the point defects. Therefore, it is considered that the effect of this embodiment can be achieved if the alkali metal salt can be expected to have this effect.
[0103] In Examples 9 to 11, it was found that the peak position of the dimensionless figure of merit ZT in the high temperature region can be shifted by preparing a mixed salt of two types of alkali metal chlorides and varying the mixing ratio. From this result, it can be seen that by adjusting the mixing ratio of two or more types of alkali metal chlorides, it is possible to manufacture a thermoelectric conversion material that exhibits better thermoelectric conversion performance in a desired high temperature region. This is thought to be because the conductive properties of the alkali metal chlorides depend on temperature. By utilizing this property, it is possible to manufacture a thermoelectric conversion material that has the desired thermoelectric conversion performance in accordance with the environment in which the thermoelectric conversion material is installed.
[0104] From the evaluation results of Examples 8 and 9, the dimensionless figure of merit ZT when calcium chloride and potassium chloride were used as a mixed salt was higher than the dimensionless figure of merit ZT when calcium chloride and sodium chloride were used as a mixed salt. In other words, it was found that calcium chloride and potassium chloride are preferable as a mixed salt of alkali metal chlorides. This is considered to be due to the fact that the amount of alkali metal chloride adsorption is large and the adsorption structure is uniform. Therefore, it is considered that a combination of alkali metal chlorides that has a large amount of adsorption and a uniform adsorption structure can improve thermoelectric conversion performance.
[0105] Conventional thermoelectric conversion materials have been produced using inorganic compounds such as lead, tellurium, bismuth, and antimony. These materials have problems such as being rare, expensive, and toxic. In contrast, the production method 1 according to the third embodiment can produce a thermoelectric conversion material using materials that are abundant on Earth and have a low environmental impact, so that it is possible to produce a thermoelectric conversion material more safely and inexpensively than conventional methods.
[0106] Furthermore, since the materials used to manufacture conventional thermoelectric conversion materials contain heavy elements, there is a problem that the weight of the conventional thermoelectric conversion materials is large. In contrast, the manufacturing method 1 according to the third embodiment can manufacture a thermoelectric conversion material using materials composed of lighter elements than conventional materials, so that a thermoelectric conversion material that is lighter than conventional materials can be manufactured.
[0107] Furthermore, most conventional thermoelectric conversion materials are used in the low temperature range from room temperature to 600°C, which means that they are not suitable for use in high temperature ranges. In contrast, the production method 1 according to the third embodiment can produce a thermoelectric conversion material that stably exhibits thermoelectric conversion performance even in the high temperature range of 600°C or higher. Therefore, the thermoelectric conversion material produced by the production method 1 according to the third embodiment can be used in high temperature environments such as nuclear power plants or boilers, thereby expanding the industrial applicability.
[0108] As described above, the manufacturing method 1 according to the third embodiment includes a mixing step S3 in which weathered biotite is mixed with an alkali metal chloride to obtain a mixture, a heat treatment step S4 in which the obtained mixture is heat-treated, a pressure molding step S5 in which the heat-treated mixture is pressure-molded to obtain a molded product, and a firing step S6 in which the obtained molded product is fired.
[0109] As a result, the manufacturing method 1 of the third embodiment can produce silicate minerals containing wadalite in a simple manner with a small environmental impact, and can also use the silicate minerals as intermediates to ultimately produce lightweight thermoelectric conversion materials that can be used in high temperature ranges safely and at low cost.
[0110] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above-mentioned embodiments, and various modifications can be made without departing from the spirit of the present invention. In the present invention, the configuration of one embodiment can be added to the configuration of another embodiment, the configuration of one embodiment can be replaced with the configuration of another embodiment, or a part of the configuration of one embodiment can be deleted. [Explanation of symbols]
[0111] 1…Manufacturing method, S1…Crushing and classification process, S2…Adsorption process, S3…Mixing process, S4…Heat treatment process, S5…Pressing and forming process, S6…Firing process
Claims
1. An adsorption step of adsorbing ions of a metal element onto a clay mineral; a mixing step of mixing the clay mineral with a salt to obtain a mixture; A heat treatment step of subjecting the mixture to a heat treatment, The clay mineral is a weathered layered clay mineral, the salt is a metal chloride that becomes a molten salt in the heat treatment step, The ionic radius of the metal element is equal to or greater than the ionic radius of the metal contained in the salt. A method for producing wadalite, comprising the steps of:
2. The clay mineral is weathered biotite; The salt is calcium chloride. A method for producing Wadalite according to claim 1.
3. The metal element is cesium. A method for producing Wadalite according to claim 2.
4. The heat treatment step heats the mixture at a heat treatment temperature of 600° C. or more and less than 850° C. A method for producing Wadalite according to claim 3.
5. The heat treatment step heats the mixture at a heat treatment temperature of 700° C. or more and less than 850° C. A method for producing Wadalite according to claim 2.
6. The adsorption step includes mixing the clay mineral with the metal element and performing a heat treatment to adsorb ions of the metal element onto the clay mineral. A method for producing Wadalite according to claim 2.
7. The adsorption step adsorbs ions of the metal element to the clay mineral by mixing the metal element with the clay mineral so that the metal element is added in an amount of 2 wt % to 6 wt % based on the weight of the clay mineral. A method for producing Wadalite according to claim 3.
8. The mixing step includes mixing the clay mineral and the salt in equal amounts by mass. A method for producing Wadalite according to claim 2.
Citation Information
Patent Citations
Method for producing wadalite compound
JP2013023400A
Method for producing photocatalyst, reduction method, and photocatalyst
JP2021070024A